High-Performance Self-Powered Dual-Mode Ultraviolet Photodetector Based on (PEA)2PbI4/GaN Heterojunction - Ang Bian; Songchao Shen; Chen Yang; Jun Dai (Nanomaterials)
Wide-bandgap semiconductors like GaN, known for their superior photoresponse and detection capabilities in the ultraviolet range, represent a foundational component in the design of advanced photodetectors, where the integration of materials with distinct spectral sensitivities into heterojunctions is pivotal for next-generation device innovation. A high-performance self-powered dual-mode ultraviolet photodetector based on a (PEA)2PbI4/GaN heterojunction was fabricated via spin coating. The device exhibits outstanding UV sensitivity under both positive and negative bias, achieving a responsivity of 1.39 A/W and a detectivity of 8.71 × 1010 Jones under 365 nm UV illumination. The built-in electric field at the heterojunction interface enables self-powered operation, achieving a rapid rise time of 46.9 ms and a decay time of 55.9 ms. These findings offer valuable insights into the development and application of perovskite and wide-bandgap semiconductor heterojunctions in optoelectronic devices.